The Effect of Minerals and Hormones on the Nutrients in Chinese Fir Leaves and Seed Set - Duan, Yu; Zhao, Linying; Ye, Daiquan; Zhou, Jian (Plants (Basel), 2025)
To investigate the impacts of various foliar fertilization levels on the carbon, nitrogen, phosphorus, and potassium content in Chinese fir cuttings, along with their ecological stoichiometry ratios, we selected pruned dwarf Chinese fir clones exhibiting different seed-setting abilities as our subjects. These clones were categorized into high-yield (group A), middle-yield (group B), and low-yield (group C) categories for nutrient assessment. Employing nine treatments of diverse fertilizers and hormones, in addition to a water control (CK), we analyzed and compared the changes in the carbon (C), nitrogen (N), phosphorus (P), and potassium (K) contents in the needles of Chinese fir clones from groups A, B, and C between 2021 and 2022. The results indicated no significant variations in the N content and C:N ratios in July among the three seed-setting characteristic Chinese fir types. However, the P content in the high-yield clones was notably higher than that in the other two types, whereas the K content was significantly lower. Following two years of continuous foliar spraying, treatments T5, T6, T8, and T9 demonstrated efficacy in enhancing the nutrient levels of branches in high-yield clones (with N content increasing by 25.07%, P content by 79.06%, and K content by 12.71%), consequently improving cone quality (as the number of cones increased by up to 256). For middle-yield clones, treatments T3, T6, and T9 exhibited promising outcomes, with respective increases in the N content, P content, and K content by 13.15%, 56.61%, and 41.31%, alongside a rise in cone number by 212. In the case of low-yield clones, the treatments T3, T4, and T5 proved effective, with increases in the N, P, and K contents by 18.54%, 36.57%, and 26.56%, respectively, as well as an increase in cone number by 82. Most treatments exhibited higher C:N ratios than the control in Chinese fir needles, whereas the N:P ratios remained below 14, indicating N limitations in the growth of Chinese fir clones. The application of N fertilizer enhanced the C:N ratios in Chinese fir needles, thereby improving nutrient absorption and utilization efficiency. Therefore, in the fertilization process of Chinese fir, tailored formulas should be employed based on the seed-setting characteristics and management objectives to achieve optimal yield enhancement.